2021
DOI: 10.1515/znc-2020-0281
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Cardenolides from the aerial parts of Calortopis procera

Abstract: Column chromatography (CC) analysis of methanol and butanol extracts of the aerial parts of Calortopis procera as well as the methanol extract of its latex, led to the isolation of 8 cardenolides, of which the structures were elucidated by NMR and HRESIMS spectroscopy. They also revealed several triterpenes and flavonoid glycoside. Based on the antiproliferative activity reported for cardenolides, the activity of calotropin and calotoxin was tested against two common cancer cell lines, human triple-negative br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A recent study (Rascón Valenzuela et al, 2015a) indicated that the IC 50 values of calotropin on the same cell line are 0.0013 µM, while antiproliferative activity was confirmed on another two cancer cell lines LS 180 (human colorectal adenocarcinoma cell line) and PC-3 (human prostate cancer cell line) with IC 50 values 0.06 and 0.41 µM, respectively. Also, the cytotoxic effects of calotropin on lung adenocarcinoma A549 cells were confirmed in the research done by Sweidan et al (2021). Interestingly, they compared the effects of calotropin on human fibroblast cell lines as normal cells and the toxicity of calotropin was lower which indicated that calotropin is more selective to cancer cells compared to normal cells.…”
Section: Lung Cancermentioning
confidence: 82%
“…A recent study (Rascón Valenzuela et al, 2015a) indicated that the IC 50 values of calotropin on the same cell line are 0.0013 µM, while antiproliferative activity was confirmed on another two cancer cell lines LS 180 (human colorectal adenocarcinoma cell line) and PC-3 (human prostate cancer cell line) with IC 50 values 0.06 and 0.41 µM, respectively. Also, the cytotoxic effects of calotropin on lung adenocarcinoma A549 cells were confirmed in the research done by Sweidan et al (2021). Interestingly, they compared the effects of calotropin on human fibroblast cell lines as normal cells and the toxicity of calotropin was lower which indicated that calotropin is more selective to cancer cells compared to normal cells.…”
Section: Lung Cancermentioning
confidence: 82%